Trivalent mRNA vaccine-candidate against seasonal flu with cross-specific humoral immune response - Mazunina, Elena P.; Gushchin, Vladimir A.; Kleymenov, Denis A.; Siniavin, Andrei E.; Burtseva, Elena I.; Shmarov, Maksim M.; Mukasheva, Evgenya A.; Bykonia, Evgeniia N.; Kozlova, Sofia R.; Evgrafova, Elina A.; Zolotar, Anastasia N.; Shidlovskaya, Elena V.; et al. (Frontiers in Immunology, 2024)
Seasonal influenza remains a serious global health problem, leading to high mortality rates among the elderly and individuals with comorbidities. Vaccination is generally accepted as the most effective strategy for influenza prevention. While current influenza vaccines are effective, they still have limitations, including narrow specificity for certain serological variants, which may result in a mismatch between vaccine antigens and circulating strains. Additionally, the rapid variability of the virus poses challenges in providing extended protection beyond a single season. Therefore, mRNA technology is particularly promising for influenza prevention, as it enables the rapid development of multivalent vaccines and allows for quick updates of their antigenic composition. mRNA vaccines have already proven successful in preventing COVID-19 by eliciting rapid cellular and humoral immune responses. In this study, we present the development of a trivalent mRNA vaccine candidate, evaluate its immunogenicity using the hemagglutination inhibition assay, and assess its efficacy in animals. We demonstrate the higher immunogenicity of the mRNA vaccine candidate compared to the inactivated split influenza vaccine and its enhanced ability to generate a cross-specific humoral immune response. These findings highlight the potential mRNA technology in overcoming current limitations of influenza vaccines and hold promise for ensuring greater efficacy in preventing seasonal influenza outbreaks.